The Designs And Performance Of Maxillary Complete Dentures In Patients With Torus Palatinus - Thein , Aye Zaw (2010)
The aim of this study was to examine the designs and performance of maxillary complete dentures in patients with torus palatinus. Maxillary impressions of one hundred and fifty patients with torus palatinus were taken and study casts were obtained using yellow stone (Calstone, France). The size of torus palatinus for individual cast was measured using MyCast (patented at Universiti Sains Malaysia) and Australis software, Version 6.01 (Photometrix, Australia) and graded into slight, moderate and marked size. Patients with slight, moderate and marked torus palatinus who were wearing maxillary complete denture were called for an appointment (n=20 patients for each group).